Raided by the storm: How three decades of thunderstorms shaped U.S. incomes and wages - Matteo Coronese; Federico Crippa; Francesco Lamperti; Francesca Chiaromonte; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
Climate change is increasingly affecting the macroeconomic performance of countries and regions. However, the effects on income inequality are less understood. We estimate the dynamic impact of thunderstorms on income and wages and reveal a robust asymmetric effect. We leverage a comprehensive dataset covering more than 200,000 events affecting contiguous US' counties across three decades. While storms' natural features are convenient for the identification of impacts, previous studies mostly focused on more extreme events. We document a robust negative association between storm activity, income and wages' growth. While income tends to recover in the long run, wages exhibit a significantly more stubborn decline, suggesting persistent and adverse impacts on (functional) income inequality. Our analyses also highlight lack of effective adaptation and stronger negative impacts in economically disadvantaged regions. Finally, we find evidence for a sizable shock-absorbing role of federal assistance.
Keywords: C14; C32; E52; 330; Storms; Natural hazards; Growth; Income Inequality; Climate change; Adaptation policies